An analysis on the legal framework for disclosure in prospectus and the standard of disclosure in determining takeovers and mergers activities post IPO - Ambaras Khan, Mushera Bibi; Arif Zakaria, Mohd Radhuan (Universiti Malaysia Sarawak, 2020)
Initial public offering (IPO) is the maiden issue of shares by a public company. The decision to go public is motivated by several motives and justifications including a motive to pursue a takeover or merger. It is crucial for the investors to predict the possibility of takeovers and mergers after IPO, so that they could make an informed decision in placing their investment. The material and relevant information contained in a prospectus relating to the IPO company could assist the investors to predict the likelihood of takeovers and mergers post IPO. Hence, this paper investigates the relevant and material information that are needed by the investors to predict the likelihood of a takeover or merger post IPO. This paper also analyse the standard of disclosure required in prospectus for initial public offering in order to determine whether the information compelled for disclosure can be used by investors to predict the likelihood of takeovers and mergers post IPO. For this purpose, the laws and regulations on capital market and securities industries as contained in the Capital Markets and Services Act 2007 and Prospectus Guidelines is analysed. The guidelines for the offering of electronic prospectus are also discussed in order to shed light on the duties of the host of e-prospectus and the safeguards for investors. The result of the study shows that the standard of disclosure in prospectus allow the investors to predict and anticipate the likelihood of takeovers and mergers post initial public offering.